PARAMETERS OF OXIDATIVE HOMEOSTASIS IN CHILDREN WITH TYPE 1 DIABETES DEPENDING ON DURATION OF THE DISEASE AND COMPLICATIONS - Shevchenko , T.; Maidannyk , V.G. (The Ukrainian Scientific Medical Youth Journal, 2018)
The increase in the number of endocrine pathology in our time is most associated with the prevalence of diabetes mellitus, which is one of the medical and social problems of modern society. According to the International Diabetic Federation (IDF) in 2015, about 415 million people in the world suffer from diabetes mellitus (DM). The purpose of our work is to study the parameters of oxidative homeostasis in children with type 1 diabetes, depending on the duration of the disease and the late complications of type 1 diabetes. Methods and materials. A total of 90 children with type 1 diabetes mellitus were diagnosed with age 13.59 ± 1.04 grams, 42 of them were girls and 48 boys with a disease duration of 4.68–3.49 grams. All children underwent treatment at the endocrinology department at the DKL No. 6, Kyiv. In the children we examined, we studied the indexes of oxidative homeostasis, namely, the products of LPO – MDA were de- termined according to the method of Stalin ID, the antioxidant system – SOD was determined according to the technique of Siroty T.V., catalase by the method of Korolyuk M.A., and reducing glutathione – by the method of Hymerha F.I. The research was conducted at the Research Institute of Experimental and Clinical Medicine of the O.O. Bogomolets NMU. Result. We detected a reliable dependence of the level of malondialdehyde on the duration of type 1 diabetes mellitus. The level of malondialdehyde increased with an increase in the duration of DM 1 type. The level of SOD the first years of the disease increased, but for 5 years the disease was reduced. The level of catalase and glutathione with decreasing durability decreases. What can be said about the depletion of the AOS and the maintenance of OS performance at a high level. There was no reliable dependence on the presence of late complications and the level of indicators of oxidative homeostasis.